ART LEARNING PROCESS TO PROMOTE EXECUTIVE FUNCTION: กระบวนการเรียนรู้ศิลปะเพื่อส่งเสริมการคิดเชิงบริหาร - Lohsomboon, Nachanok; Boonyananta, Soamshine (Journal of Education and Innovation, 2020)
Prefrontal cortex has ability in management dimension which involves in the planning of complex behaviors, personality expression and decision. It is coordinated with other brain parts and is also called executive function. It will be highly developed during the age of 4 - 5 years. Therefore, this is an important opportunity for development through design thinking process that relates with prefrontal cortex function by learning management in art activities that are tools for happiness learning management. The art learning processes are including in four stages: 1) share, 2) plan, 3) act, and 4) show.